Hubungan Konsep Diri Dengan Resiliensi Pada Remaja Di SMA N 1 Kedungwuni - Lestari, Yulia Mega; Nafiah, Hana (PENA NURSING, 2024)
Adolescents experience physical and psychological changes, making them vulnerable to external influences. The lifestyles of those around them easily sway their identity-finding process, and they often take shortcuts without considering the consequences. Adolescent resilience depends on self-concept. Resilient adolescents must be strong-willed, uninfluenced, and positive in adverse situations. The design of this study used a description correlation with a cross- sectional approach. A proportionate stratified random sampling technique was used to sample 240 respondents. Marlen S's self-concept and resilience scales from Wagnild and young questionnaires adapted by Aptini Dwi were used as the instrument. Pearson correlation was used to analyse data. The findings indicated that the mean age of the participants was 16.24 years. Approximately 74.2% of the population identifies as female. All participants identify as followers of the Islamic faith. Most participants (93.5%) did not have prior experience attending a boarding junior high school. Most participants reside in households with both their biological mother and father (97.5%), and the prevailing marital status of the respondents' parents is that they remain in a committed relationship (82.9%). The self-concept variable had an average score of 116.65 (±13,782), whereas resilience had an average score of 118.15 (±21,372). The analysis findings indicate a statistically significant association between self- concept and adolescent resilience, with a p-value of 0.000 (p <0.05). Furthermore, the correlation between these two variables is modest, with a coefficient of r = .542.